2020
DOI: 10.1002/bit.27313
|View full text |Cite
|
Sign up to set email alerts
|

Non‐carbon loss long‐term continuous lactic acid production from mixed sugars using thermophilic Enterococcus faecium QU 50

Abstract: In this study, a non‐sterile (open) continuous fermentation (OCF) process with no‐carbon loss was developed to improve lactic acid (LA) productivity and operational stability from the co‐utilization of lignocellulose‐derived sugars by thermophilic Enterococcus faecium QU 50. The effects of different sugar mixtures on LA production were firstly investigated in conventional OCF at 50°C, pH 6.5 and a dilution rate of 0.20 hr−1. The xylose consumption ratio was greatly lower than that of glucose in fermentations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Panesar et al [37] reported the production of 33.73 g•L −1 L-LA using L. casei, while Taleghani et al [38] reported a value of 32.1 g•L −1 when whey was fermented by L. bulgaricus. Molasses derived either from sugarcane or sugar beets fermentation to lactic acid has also been investigated, using various LAB strains [39][40][41]. In the recent work of Sun et al [41], a microbial consortium in which Clostridium sensu stricto was the predominant strain was tested for sugarcane molasses fermentation to lactic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Panesar et al [37] reported the production of 33.73 g•L −1 L-LA using L. casei, while Taleghani et al [38] reported a value of 32.1 g•L −1 when whey was fermented by L. bulgaricus. Molasses derived either from sugarcane or sugar beets fermentation to lactic acid has also been investigated, using various LAB strains [39][40][41]. In the recent work of Sun et al [41], a microbial consortium in which Clostridium sensu stricto was the predominant strain was tested for sugarcane molasses fermentation to lactic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that continuous fermentation process is advantageous for high LA productivity due to dilution of the produced LA in the broth resulted from feeding new medium and high operational stability by achieving steady state of cell growth. The LA production, and sugar consumption, compared with batch or fed-batch fermentation processes where usually difficult to sustain homogeneities in large scales [15,16,46]. It was suggested that continuous SSF with enzyme addition and cell recycle can solve the problems caused by feedback, substrate and end-product inhibition compared to batch or fed-batch fermentation while resulting in higher LA productivities, yield, and concentration [47].…”
Section: Larger Scale Fermentation For Carobmentioning
confidence: 99%
“…It was suggested that continuous SSF with enzyme addition and cell recycle can solve the problems caused by feedback, substrate and end-product inhibition compared to batch or fed-batch fermentation while resulting in higher LA productivities, yield, and concentration [47]. Several recent studies showed that continuous fermentation with cell recycle resulted in a higher LA productivity, and when the cells reached a steady-state, a high LA level was maintained for longer time and the utilization of the sugars was at maximum to produce LA (7,15). In addition, these studies have shown that, the lag phase in the cells was reduced, the operational cost was lower, and resulted in the increase of LA production (7,15).…”
Section: Larger Scale Fermentation For Carobmentioning
confidence: 99%
See 1 more Smart Citation
“…xylose as substrates during the single and mixed sugar fermentation. Substrates and production inhibitions were observed in the batch fermentation experiments with E. mundtii QU 25 [22,23]. The cell growth was defined by Monod kinetics with substrate and production inhibition terms as shown in…”
Section: Model Developmentmentioning
confidence: 99%